2017
DOI: 10.3847/2041-8213/aa6fb4
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Tails around the Outer Halo Globular Clusters Eridanus and Palomar 15

Abstract: We report the discovery of tidal tails around the two outer halo globular clusters, Eridanus and Palomar 15, based on gi-band images obtained with DECam at the CTIO 4-m Blanco Telescope. The tidal tails are among the most remote stellar streams presently known in the Milky Way halo. Cluster members have been determined from the color-magnitude diagrams and used to establish the radial density profiles, which show, in both cases, a strong departure in the outer regions from the best-fit King profile. Spatial de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 45 publications
3
57
1
Order By: Relevance
“…In Figure 7 we show our density contour map for Eridanus. Morphologically, the map shows no remarkable or unusual features, and its number density profile is well fitted by either a King or Sérsic model and thus we cannot confirm the presence of a tidal structure around Eridanus, although we note that Myeong et al (2017)'s data are at least one magnitude deeper than ours. 4.4.7.…”
Section: Fornaxcontrasting
confidence: 88%
See 1 more Smart Citation
“…In Figure 7 we show our density contour map for Eridanus. Morphologically, the map shows no remarkable or unusual features, and its number density profile is well fitted by either a King or Sérsic model and thus we cannot confirm the presence of a tidal structure around Eridanus, although we note that Myeong et al (2017)'s data are at least one magnitude deeper than ours. 4.4.7.…”
Section: Fornaxcontrasting
confidence: 88%
“…Palomar 15's overall ellipticity is = 0.05 ± 0.02 and its two-dimensional morphology shows no irregularities or signs of tidal interaction (Figure 15). We note that Myeong et al (2017), using photometry taken with the DECam imager on the 4m Blanco telescope at CTIO, reports the presence of tidal-like substructure on the outskirts of Palomar 15. 4.4.37.…”
Section: Palomar 15mentioning
confidence: 82%
“…At this point, it is not possible the assess whether that extra-tidal structure reveals the existence of tidal tails. Indeed, some GGCs with a break in the radial density profiles -like the one observed in Fig 2 (left panel) -present tidal tails (e.g., Eridanus and Pal 15; Myeong et al 2017), while others do not (e.g., NGC 1261 and NGC 7089; Kuzma et al 2016Kuzma et al , 2017. In order to address this issue, we investigated whether the resultant stellar density radial profile may vary with the orientation from the cluster centre.…”
Section: Star Countsmentioning
confidence: 73%
“…Piatti (2017a) also found a similar feature around 47 Tuc. Other GGCs were found to be embedded in a diffuse stellar envelope extending to a radial distance of at least five time the nominal tidal radius, like M 2 (Kuzma et al 2016); and long tidal tails have been detected in the field of Pal 5 (Odenkirchen et al 2003), Pal 14 (Sollima et al 2011), Pal 15 (Myeong et al 2017), and NGC 7492 (Navarrete et al 2017). As far as theoretical developments are considered, some Nbody experiments have shown that the detection of extended envelopes around GGCs could be due to potential escapers (Küpper et al 2010) or potential observational biases (Balbinot & Gieles 2017), among others.…”
Section: Introductionmentioning
confidence: 99%
“…However, an important conclusion of our present investigations is that the final asymmetry as well as the dynamical properties of the remnant are very sensitive to the orbit and initial conditions for the progenitor, so that no conclusion can be reached without modelling each different stream separately. Other potentially interesting streams for further studies are those recently discovered around Eridanus, Palomar 15 (Myeong et al 2017) or the PS-1 C stream around the Balbinot 1 GC (Bernard et al 2016;Balbinot et al 2013). …”
mentioning
confidence: 99%